Deterring predator pursuit and attracting potential mates? The conspicuous melanized tail display of the zebra-tailed lizard. Issue 2 (4th March 2023) - Reed, Abigail A.; Lattanzio, Matthew S.
Abstract : The evolutionary significance of color expression in animals is often framed within either an interspecific (e.g., antipredator display) or intraspecific (e.g., mate choice) context. In part, this dichotomy stems from assumptions that the expression of conspicuous sexually selected traits likely hinders survival in the wild. Here we address the potential for natural and sexual selection to reinforce expression of a conspicuous tail bar pattern in zebra-tailed lizards ( Callisaurus draconoides ). In C. draconoides, display of this tail bar pattern has historically been considered an interspecific signal to deter predator pursuit. However, a putative honest link between the tail bar pattern and escape likelihood (e.g., sprint speed) is unknown. Further, studies on related taxa also support the potential for this trait to be informative as a signal of individual quality during mating interactions as well. We assessed variation in the morphology of male and female C. draconoides, and then evaluated how variation in morphology (emphasizing the tail bar pattern) contributed to variation in performance (sprint capacity) and, for males, variation in female preference. Males were larger than females, but size was unrelated to variation in tail bar number. Males sprinted faster than females overall, but tail bar number only mattered for males: specifically, males with more tail bars sprinted faster. Females also preferred males with more tail bars. Overall, our findings suggest that natural (mediated via an honest link between bar number and sprint speed) and sexual (mediated via a preference for males with more tail bars) selection may mutually reinforce expression of a color signal. Thus, the potential adaptive benefits of a color signal may span intra- and interspecific contexts. For males at least, the tail bar pattern is useful for both deterring the pursuit of predators as well as attracting the attention of potential mates.